Building Students’ Historical Awareness through Local History of Pue Lasadindi: A Descriptive Qualitative Study at SMAN 5 Palu - Melisa Melisa; Juraid Abdul Latief; Iskandar Ahmad; Mahfud M Gamar (FKIP - Universitas Riau, 2026)
The research investigates how SMAN 5 Palu students build their historical knowledge through local history studies about Pue Lasadindi. The research is motivated by the low level of students’ understanding and awareness of local history, which is often less emphasized in classroom learning. The researchers utilized qualitative descriptive research method to investigate how the implementation process affects student learning outcomes. The research team collected data through observation and interviews and documentation work which included the school principal and one history teacher and students from class X Merdeka. The results show that using local historical knowledge in history education together with interactive learning materials and Problem Based Learning methods increases student participation and makes learning easier for them. Students demonstrate improved historical awareness reflected in their ability to appreciate local heroes, understand historical values, and develop a sense of identity and nationalism. The teacher establishes essential learning activities which help students connect their historical knowledge to their everyday experiences. The study shows that local history helps students learn both cognitive and emotional skills, so historians should use it more systematically in their teaching to enhance students' historical understanding.